2016
DOI: 10.1364/ome.6.001451
|View full text |Cite
|
Sign up to set email alerts
|

As_4S_4 role on the photoinduced birefringence of silver-doped chalcogenide thin films

Abstract: Ag X (As 40 S 60) 100-X thin films (x = 7, 15, 25, 50) were deposited on glass slides by a co-evaporation technique under a vacuum. Photoinduced birefringence was induced using light provided from a continuous argon-ion laser operating at 488 nm. We investigated the impact of silver concentration and laser power density. The thin films structural changes after irradiation were characterized by Raman spectroscopy, indicating that addition of Ag induces the breaking of sulfur ring units and favors the creation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 29 publications
(29 reference statements)
1
2
0
Order By: Relevance
“…Messaddeq et al prepared Ag x (As 40 S 60 ) 100x thin films (x ¼ 7, 15, 25, and 50) by co-evaporation technique and studied the role of As 4 S 4 molecules on the photoinduced birefringence of these thin films. [13] The calculated density of states (DOS) based on s, p (sigma), and p lone pair orbitals was close to the experimental photoemission data, and it was found that As 2 S 3 and As 2 Se 3 had indirect gaps. Watanabe et al [14] used a tight-binding method to calculate energy bands of crystalline As 2 S 3 and random configurations of macromolecules in a-As 2 S 3 and suggested that intermolecular configuration and interactions in crystalline chalcogenides greatly affect the electronic structure.…”
Section: Introductionsupporting
confidence: 61%
“…Messaddeq et al prepared Ag x (As 40 S 60 ) 100x thin films (x ¼ 7, 15, 25, and 50) by co-evaporation technique and studied the role of As 4 S 4 molecules on the photoinduced birefringence of these thin films. [13] The calculated density of states (DOS) based on s, p (sigma), and p lone pair orbitals was close to the experimental photoemission data, and it was found that As 2 S 3 and As 2 Se 3 had indirect gaps. Watanabe et al [14] used a tight-binding method to calculate energy bands of crystalline As 2 S 3 and random configurations of macromolecules in a-As 2 S 3 and suggested that intermolecular configuration and interactions in crystalline chalcogenides greatly affect the electronic structure.…”
Section: Introductionsupporting
confidence: 61%
“…In our recent work [39], it was demonstrated that due to the incorporation of Ag in the As-S thin-film, a structural rearrangement favouring the appearance of AgS 3/2 pyramids and As 4 S 4 molecules are formed. In order to explain the polarisation dependence of the laser-dewetted surface relief structure, we can assume that at the early stage of irradiation by a linearly polarised laser, structural As 4 S 4 cages units are reoriented and serve as anisotropic sensitive structural units.…”
Section: Effects Of the Thicknessmentioning
confidence: 97%
“…Revutska et al [ 11 ] characterized As 2 S 3 glasses doped by 10 and 15 wt% Ag. Sandra et al [ 12 ] studied the role of As 4 S 4 molecules on the photoinduced birefringence of Ag x (As 40 S 60 ) 100− x thin films ( x = 7, 15, 25, 50). The bandgap tuning was observed [ 13 ] by X‐ray powder diffraction (XRPD) studies of Se‐, Cu‐, and Zn‐doped Sb 2 S 3 nanoparticles and dielectric constant of Cu‐doped Sb 2 S 3 was found between 2.10 and 2.45.…”
Section: Introductionmentioning
confidence: 99%